O07.2 Use of whole-genome sequencing to identify sexual transmission of shigella in men who have sex with men in england. (14th July 2019) - Mitchell, Holly; Mikhail, Amy; Painset, Anaïs; Dallman, Timothy; Jenkins, Claire; Thomson, Nicholas; Field, Nigel; Hughes, Gwenda
Abstract : Background: In 2015, routine whole-genome sequencing (WGS) of Shigella spp. was introduced by Public Health England (PHE) to identify transmission clusters, but limited behavioural information hampers interpretation. We investigated whether WGS can distinguish between clusters of sexual transmission among men who have sex with men (MSM) and other modes of transmission. Methods: WGS data for non- sonnei Shigella were sorted into clusters based on single nucleotide polymorphism (SNP) typing at various SNP distances (standard is 10-SNPs). Clusters were defined as 'household', 'travel-associated', 'community' or 'adult male' using data submitted with laboratory isolates (age, gender and foreign travel). PHE contacted cases to pilot a new exposure questionnaire, including information on sexual behaviour, from July 2015-March 2017. Questionnaire data were used to validate whether 'adult male' clusters represented likely sexual transmission between men. Results: 201 isolates had questionnaire and linked WGS data, of which 106 clustered with at least one other isolate (10-SNPs). 95.1% (77/81) of self-reported MSM belonged to an 'adult male' cluster and 4.9% (4/81) to a 'community' cluster; most (74.1%; 60/81) reported recent same-sex sexual contact. 70.6% (12/17) of non-MSM belonged to a 'community' cluster, 23.5% (4/17) to an 'adult male' cluster and 5.9% (1/17) to a 'travel-associated' cluster. 73.2% (71/97) of all MSM isolates belonged to the same phylogenetic lineage; for which 10-SNP clustering identified multiple discrete clusters (7 'adult male'; 2 'community') suggesting they should be re-classified as a single 'adult male' cluster. Genetic markers of azithromycin resistance were detected in 84.7% (304/359) of 'adult male' and 20.5% (9/44) of other clusters. Conclusion: Our study suggests that SNP clustering can be used to identify Shigella transmission in MSM with high precision to inform infection control. Defining clusters requires a flexible approach in terms of genetic relatedness to avoid misclassification or unnecessary follow-up of clusters that may belong to the same transmission network. Disclosure: No significant relationships.